Pengaruh Penggunaan Aplikasi Olahraga Terhadap Self-Presentation Pada Generasi Z - Shofila Hilma Faradiana Nandita Putri; Miftakhul Jannah (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
The purpose of this study was to evaluate the impact of sports app use on how individuals present themselves in the context of Generation Z, who grew up in the digital era and have the potential to express their identity through online platforms. Using quantitative methods, this study involved 136 Generation Z participants aged 15-25 who actively used digital-based sports apps. Data were collected using the Self-Presentation Tactics Scale – Assertive (SPRS; Lee et al., 1999) and the sports app usage scale developed by Baubonytė and Deliautaitė (2021). Data were then analyzed using JASP with validity, reliability, descriptive analysis, classical assumptions, and simple linear regression tests. The study findings showed that sports app use had a significant positive effect on self-presentation (p < 0.001) with a contribution of 62.2%, indicating that the higher the intensity of sports app use, the greater the tendency for individuals to actively present themselves in digital spaces. This research suggests that sports app developers consider users' social and self-identity aspects as part of their strategies to increase digital engagement and participation. Keywords: sports apps, self-presentation, Generation Z, digital media